Giant Fibrolipoma in the Distal Limb of a Cow - Queiroz, Paulo José Bastos; Caixeta, Paulo César Machado Mattos; Nascente, Eduardo de Paula; Silva, Danilo Conrado; Rabelo, Rogério Elias; Silva, Luiz Antônio Franco da (Acta Scientiae Veterinariae, 2021)
Background: Lipomas are adipocytic tumors of slow and expansive growth. They can be classified into several subtypes depending on the tissue present next to the neoplastic adipocytes. One of such subtypes is the fibrolipoma, which is formed by well-differentiated adipocytes and fibrous connective tissue. This neoplasm has been little described in cattle, and rare reports present the treatment and resolution of the case. Thus, the dissemination of cases of fibrolipomas in cattle is essential to help veterinarians diagnose this neoplasm. The present report describes a case of fibrolipoma in the distal pelvic limb of a cow successfully treated by surgical excision. Case: A 4-year-old 3/4 Girolando cow from the municipality of Vazante-MG, Brazil, was treated on the farm. According to the owner, the animal had been showing tumoral growth in the left pelvic limb over the period of 1 year and 3 months. The tumor involved the entire left metatarsus and was 40 x 37 cm, without ulcerations and painless on palpation. A neoplasm was suspected and surgical excision was the chosen approach. The cow was sedated, positioned and restrained in right lateral recumbency for surgery. The operative field was prepared and a subcutaneous locoregional ring block was performed dorsally to the tumor. The tumor mass was excised with a safety margin of 1 cm. After removal, the mass was found to weigh 10.4 kg and to be yellowish-white upon sectioning. Due to the distance between the edges of the surgical wound, skin suture could not be performed. Thus, second-intention healing and wound protection with bandages were the choice of management. In the postoperative period, the adopted treatment consisted of antibiotic therapy with benzathine penicillin, analgesia with non-steroidal anti-inflammatory drugs, daily dressings and wound protection with bandages. The animal did not show postoperative complications and, over 8 months of monitoring after surgery, there was no recurrence of the neoplasm and the cow was in productive activity. Tumor fragments were fixed in 10%buffered formalinand sent for histopathological examination, which revealed a neoplasm of mesenchymal cells in the subcutaneous adipose tissue supported by dense fibrovascular stroma with solid arrangement. A large amount of dense connective tissue was found among the neoplastic cells. In view of these findings, the diagnosis of fibrolipoma was established. Discussion: Fibrolipoma is a benign neoplasm little described in the veterinary literature, especially in cattle, with only 3 cases reported. To the knowledge of the authors, this is the first report of this neoplasm in the distal limb of cattle. Fibrolipomas are a rare type of lipoma formed by well-differentiated lipocytes and fibrous tissue. The fibrolipoma described in this report was 40 cm in diameter and weighed 10.4 kg, so it can be classified as a type of giant lipoma, as it was more than 10 cm in diameter and more than 1 kg in weight. In the present report and in others in the medical literature, surgical removal of the fibrolipoma resulted in complete recovery of the patient without postoperative complications. Surgical excision is the treatment of choice in these cases and usually promotes healing. However, surgery must be performed early and the neoplasm must be completely removed. The histological characteristics of the fibrolipoma in this case are similar to those found in other cases in cattle and corroborate the choice for surgical treatment and maintenance of the animal in the herd. Although rare, fibrolipomas should be included in the differential diagnosis of tumors of slow and expansive growth in cattle. Keywords: bovine, adipose tissue, lipoma, neoplasia, surgery. Descritores: bovino, cirurgia, tecido adiposo, lipoma, neoplasia. Título: Fibrolipoma gigante no membro distal de uma vaca